Strategi Media Televisi dalam Menjalankan Corporate Social Responsibilities Jembatan Asa SCTV - Bagoes Arie Oetomo; Enda Surya (Universitas Medan Area, 2021)
This study aims to know television in carrying out the CSR program of Jembatan Asa SCTV. The research method used is a qualitative method, using interview techniques with resource persons SCTV Corporate Communication. The targets of this CSR program are residents of Sipak Village, Jasinga District, Kab. Bogor. In this research, it was found that the strategy used for CSR. The Asa Bridge is an introduction to society or beliefs, selecting messages, determining methods as well as selecting and selecting media. However, the communication strategy included in the measured evaluation has not been carried out properly by SCTV. The conclusion of the research is that for the implementation of a good CSR program from planning to implementing it is not easy, good communication, good coordination, as well as qualified cooperation, within the company or external needs between companies and with interests is needed. The results and benefits obtained from the CSR program must be disseminated to the public for accountability and corporate transparency. Communication carried out in the CSR Asa SCTV program is carried out through a series of methods and activities to reach the target audience as the beneficiaries of the CSR program.